The Effectiveness of Media Flipchart 活动挂图 in Learning Chinese Vocabulary for Students Aged 8-9 Years at Makassar Mandarin Language Centre - Mir'ah Azizah; Ria Riski Marsuki (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2023)
This research was conducted to measure the level of effectiveness of flipchart 活动挂图 media in learning Chinese vocabulary. This study applies the quantitative-qualitative research method in quadrant I, namely by using a pre-test to measure students' abilities before flipchart media is applied in learning Mandarin, flipchart media, a post-test to measure students' abilities after learning Mandarin using flipcharts, and guidelines observation in the research instrument. The sample for this study was 15 students aged 8-9 years at the Mandarin Language Center in Makassar. Based on the research results, the students were very enthusiastic in learning Chinese vocabulary using flipcharts, and the class atmosphere became very enjoyable. In addition, students' ability to master Chinese Vocabulary has increased after applying flipcharts 活动挂图. The average score of the students in the pre-test was 53, which was classified as a terrible score. After the flipchart media is applied in learning Mandarin, the general average of students in the Post-test is 86.33, which is in a very good score classification. This shows that using flipchart media is very effective in learning Chinese vocabulary.